1999
DOI: 10.1161/01.cir.99.17.2255
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between a Polymorphism of the Aldosterone Synthase Gene and Left Ventricular Structure

Abstract: The data are not in favor of a significant contribution of the C/T exchange at position -344 in the aldosterone synthase transcriptional regulatory region to the variability of serum aldosterone levels, blood pressure, or cardiac size or function as found in 2 white population-based samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
5
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 23 publications
2
82
5
5
Order By: Relevance
“…In keeping with the results of earlier studies, the associations of the CYP11B2 C-344T polymorphism with BP remain inconclusive. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In addition, our results were not consistent with previous reports indicating that BP elevation was sensitive in elderly subjects with the TT genotype. 20,21 Furthermore, we suggested that the association of the CC genotype with CRP was consistent with previous reports describing the association of the genotype with cardiac structures and atherosclerosis as discussed above, 17,34 whereas some apparent contradictory associations between the genotype and atherosclerosis, including cardiac structure and coronary artery diseases, have been shown in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In keeping with the results of earlier studies, the associations of the CYP11B2 C-344T polymorphism with BP remain inconclusive. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In addition, our results were not consistent with previous reports indicating that BP elevation was sensitive in elderly subjects with the TT genotype. 20,21 Furthermore, we suggested that the association of the CC genotype with CRP was consistent with previous reports describing the association of the genotype with cardiac structures and atherosclerosis as discussed above, 17,34 whereas some apparent contradictory associations between the genotype and atherosclerosis, including cardiac structure and coronary artery diseases, have been shown in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…3 An overview of published studies suggests a higher frequency of hypertension or increase in blood pressure (BP) in subjects with the T allele or TT genotype as compared with that in subjects with the C allele or CC genotype, [4][5][6][7][8][9][10] although several studies have reported the opposite association 11,12 or the absence of any association. [13][14][15][16][17][18][19] Thus, the associations remain controversial. Recently, two interesting studies have suggested a key indicator that may resolve the association.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study on a larger but older population failed to confirm the association between C(À344)T polymorphism and BP, cardiac measurements, and aldosterone levels. 2 Further contradictory results came from another paper that described both a linkage study on hypertensive sibships and a casecontrol study. 3 These studies, based on older populations than Kupari's, 1 failed in finding a linkage of hypertension with CYP11B2 alleles, but found a positive association of the T(À344) allele with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…73 Although one small study confirmed this association, 74 other larger studies failed to detect a significant effect of this polymorphism on left ventricular structure. 75,76 Mayosi et al 77 investigated the contribution of several markers in the CYP11B2 gene, including the C-344T polymorphism, as individual variants and haplotypes. Polymorphisms and haplotypes at the CYP11B2 locus were associated with a small but significant effect on variation in septal wall thickness and left ventricular cavity size (variants G5937C and A4450C respectively).…”
Section: Aldosterone Synthase C-344t Polymorphismmentioning
confidence: 99%